(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
As the world becomes more interconnected, there is a corresponding rise in the amount of interaction between people from various social groups, which creates more opportunities than ever for prejudice-based discrimination. The underlying assumption of this article is that prejudice is largely influenced by language. This review concludes that language plays a crucial role in all forms of prejudice and that prejudice can have an implicit as well as an explicit impact on language. This strongly implies that prejudice and language are not only inextricably linked, but that studying prejudice without taking language into account is incomplete.